ECONOMETRIC ANALYSIS OF THE ECONOMIC GROWTH OF THE REPUBLIC OF UZBEKISTAN IN THE CONDITIONS OF THE DIGITAL ECONOMY - Egamberganov J.K.; Ismailov D. (Scholars Digest Publishing, 2022)
The article describes the scientific and practical aspects of the econometric analysis of economic growth in Uzbekistan in the context of an extensive, intensive and digital economy. It also analyzes the pros and cons of ensuring the quality of economic growth in an extensive, intensive and digital economy.
Keywords: intensive factors, digital economy, econometric analysis, comparative analysis